The Impact of Social Support and Pregnancy on Subjective Well-Being: A Systematic Review - Battulga, Buyantungalag; Benjamin, Marc Reginald; Chen, Hong; Bat-Enkh, Enkhmandakh (Frontiers in Psychology, 2021)
Background: Subjective well-being (SWB) has a protective role in mental health maintenance, and is prone to change during short stressful moments, such as pregnancy. Longstanding research suggest that social support (SS) from their partner and family member of pregnant women directly or indirectly acts as a buffer against negative mental outcomes. For happier pregnancies, it is important to understand how SS and pregnancy are affecting the SWB. Objective: This review aims to examine the extend association of being pregnant and SS on the SWB of pregnant women. Methods: A systematic literature search was conducted in PubMed, ScienceDirect and Google scholar. Articles were included if they had been published in peer-reviewed journals regardless of year and assessed the impact of at least one SWB or SS outcome among healthy pregnant women. The National Heart, Lung, and Blood Institute's tools were used for quality assessment. Results: 33 studies that assessed the domains of SWB measurements, such as happiness, quality of life (QoL), life satisfaction, positive and negative affect, wellbeing were included and summarized in its association with either pregnancy or SS. Variable results were found during pregnancy, as life satisfaction, happiness, mental component of QoL were high but positive emotion and physical component of QoL had decreased. Almost universally, SS during pregnancy was found to have a positive association with all measurements of SWB. Conclusion: Our study indicates that, despite some emerging trends, pregnancy itself does not necessarily have similar impacts on SWB across healthy pregnant women. However, social support had significant effect on SWB.